Effect of Cultural Factors on Speech Perception in Multilingual Contexts in United Kingdom - Brown, Emily (International Journal of Linguistics, 2024)
Purpose: The aim of the study was to analyze the effect of cultural factors on speech perception in multilingual contexts in United Kingdom. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Cultural factors significantly influence speech perception in multilingual contexts in the United Kingdom, impacting individuals' ability to discern phonetic contrasts across languages. Language exposure, cultural identity, and social interactions all contribute to shaping speech perception abilities among multilingual speakers. Considering socio-cultural context is crucial in understanding these phenomena, as cultural norms and values influence auditory processing mechanisms. Unique Contribution to Theory, Practice and Policy: Social identity theory, acculturation theory & communication accommodation theory may be used to anchor future studies on analyze the effect of cultural factors on speech perception in multilingual contexts in United Kingdom. Develop culturally responsive language education programs that recognize and celebrate linguistic diversity. Advocate for policies that promote linguistic and cultural inclusivity in education, workplace, and public services.